Psychosocial aspects of Hansen's disease (leprosy) - Gurvinder Pal Singh (Wolters Kluwer Medknow Publications, 2012)
In general, the prevalence of psychiatric disorders among people with Hansen's disease has greatly increased to date. However, inadequate psychiatric care of people with Hansen's disease is an area of increasing concern. Many studies have been conducted in India and abroad to find out the prevalence of comorbid psychiatric disorders in patients suffering from Hansen's disease. Although efforts have been made by the government and international organizations to solve the medical problems among this group of patients, this disease still carries a number of psychosocial issues. The social stigma connected to these patients makes this disease completely different from others. Even nowadays people affected by Hansen's disease have to leave their village and are socially isolated. Depression is the most common psychiatric disorder found in these patients. Early detection and treatment of psychiatric disorders among Hansen's disease patients is a powerful psychotherapeutic measure. Integrated healthcare strategy will be beneficial to these patients. A comprehensive MEDLINE search and review of relevant literature was carried out and the data extracted and studied with particular reference to psychosocial issues in Hansen's disease. The focus of this research work is related to psychiatric and social aspects vis-à-vis stigma in these patients with Hansen's disease.